Reliability and structural validity of the Danish Short 4-item version of the Center for Epidemiological Studies Depression Scale for Children (CES-DC4) in adolescents - Christine Leonhard Birk Sørensen; Therese Koops Grønborg; Karin Biering (BMC, 2022)
Abstract Background The 4-item version of the Center of Epidemiological Studies Depression Scale (CES-DC4) is a self-reported questionnaire used to measure depressive symptoms in adolescents, but the psychometric properties of the scale have been tested to only a limited extent. The aim of this study was to examine the reliability and structural validity of the Danish CES-DC4 in 9th graders. Methods Using a sample of 72 adolescents 15 to 17 years of age from five 9th grade classes, the reliability of the CES-DC4 was determined by a test-retest study at a 2-week interval. Descriptive statistics of the adolescents were presented, and internal consistency, structural validity, reliability, and agreement between tests were evaluated. The structural validity of the scale was tested by confirmatory factor analysis (CFA), and the sumscores of the test and retest were presented. Results The estimated Cronbach's α was 0.61 (95% CI 0.50; 0.71). Inter-item and item-rest correlations indicated that one of the four items (item 20) did not fit well on the scale. CFA found a one-factor model suited for the scale, but the factor loadings indicated that item 20 contributed the least to measure the factor (0.29). Sum scores ranged from 0-9 within a possible interval of 0-12. There were no signs of systematic error of the scale. Limits of Agreement (-3.01; 3.79) were broad. The standard error of measurement (SEM = 1.25 point (95% CI.1.05; 1.47)) and intraclass correlation (ICC(2,1) = 0.60 (95% CI: 0.44; 0.73)) calculations showed low reliability of the CES-DC4. Conclusion This study found low reliability of the CES-DC4 with low estimates of ICC and Cronbach's α. The CES-DC4 needs revision, and removal of item 20 and adding more items from the CES-DC should be considered.